“The greatness of a writer consists in articulating the eternal problems and dilemmas of humanity”: An Interview with Professor Hubert Orłowski, Conducted by Karolina Król - Król, Karolina; Orłowski, Hubert (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2020)
The interview focuses on Thomas Mann, his oeuvre and the reception of his works. The dispute around Mann’s The Magic Mountain, started by Stanisław Barańczak, is an important context of the text. In the interview an essay Reflections of a Nonpolitical Man (yet untranslated into Polish as a whole) is mentioned.